Enoxacin Elevates MicroRNA Levels in Rat Frontal Cortex and Prevents Learned Helplessness - Smalheiser, Neil R.; Zhang, Hui; Dwivedi, Yogesh (Frontiers in Psychiatry, 2014)
Major depressive disorder (MDD) is a major public health concern. Despite tremendous advancement, the pathogenic mechanisms associated with MDD are still unclear. Moreover, a significant number of MDD subjects do not respond to the currently available medication. MicroRNAs (miRNAs) are a class of small non-coding RNAs that control gene expression by modulating translation, mRNA degradation or stability of mRNA targets. The role of miRNAs in disease pathophysiology is emerging rapidly. Recently, we reported that miRNA expression is down-regulated in frontal cortex of depressed suicide subjects, and that rats exposed to repeated inescapable shock show differential miRNA changes depending on whether they exhibited normal adaptive responses or learned helpless behavior. Enoxacin, a fluoroquinolone used clinically as an antibacterial compound, enhances the production of miRNAs in vitro and in peripheral tissues in vivo, but has not yet been tested as an experimental tool to study the relation of miRNA expression to neural functions or behavior. Treatment of rats with 10 or 25 mg/kg enoxacin for one week increased the expression of miRNAs in frontal cortex and decreased the proportion of rats exhibiting learned helpless behavior following inescapable shock. Further studies are warranted to learn whether enoxacin may ameliorate depressive behavior in other rodent paradigms and in human clinical situations, and if so whether its mechanism is due to upregulation of miRNAs.